2016
DOI: 10.1097/anc.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Wolff–Parkinson–White Syndrome in a Term Infant Presenting With Cardiopulmonary Arrest

Abstract: Nurses caring for infants should be alert to tachycardia and irregularities of the heart rate, including those in the prenatal history, and should report them for evaluation. While all parents should be taught to watch for signs of illness, parents of infants with Wolff-Parkinson-White have additional learning needs, including recognizing early signs and symptoms of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(55 citation statements)
references
References 15 publications
1
54
0
Order By: Relevance
“…Particular care must be taken with infants, in whom it is challenging to determine the absence of symptoms and therefore, to determine the real risk by the clinical history alone remains a dilemma. Remarkably, the incidence of SCD seems to be higher in pediatric than adult patients (1.93 versus 0.86 per 1,000 person-years) 11 , and SCD may be the initial symptom in up to 53% of cases [5][6][7][8]14,15 . Also, it is essential to bear in mind that the unavailability of ECG during resuscitation could underestimate the low incidence of infants presenting with SCD.…”
Section: Real Risk Of Sudden Cardiac Death In Asymptomatic Patientsmentioning
confidence: 98%
See 3 more Smart Citations
“…Particular care must be taken with infants, in whom it is challenging to determine the absence of symptoms and therefore, to determine the real risk by the clinical history alone remains a dilemma. Remarkably, the incidence of SCD seems to be higher in pediatric than adult patients (1.93 versus 0.86 per 1,000 person-years) 11 , and SCD may be the initial symptom in up to 53% of cases [5][6][7][8]14,15 . Also, it is essential to bear in mind that the unavailability of ECG during resuscitation could underestimate the low incidence of infants presenting with SCD.…”
Section: Real Risk Of Sudden Cardiac Death In Asymptomatic Patientsmentioning
confidence: 98%
“…A randomised clinical trial that evaluated the results of prophylactic catheter ablation in children (aged 5-12 years) with AWPWS showed that the absence of prophylactic ablation was an independent predictor of arrhythmic events 12 . However, EPS is an invasive procedure with a risk of complications (5%-15%), with major ones reported in 0.9%-4.2% (death 0.12%), being higher in infants less than 15kg of weight or 18 months of age [5][6][7][8][16][17][18][19] . Also, prolonged exposure to radiation and high recurrence rates of arrhythmia after successful procedures (7%-17%) are of particular concern [5][6][7][8][16][17][18][19] .…”
Section: Invasive Risk-stratificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary valve or supravalvular pulmonary stenosis have been well described with RASopathies, such as Noonan and Casitas B‐cell lymphoma (CBL) syndrome, which are among the more common genetic syndromes underlying NIHF . Cardiac arrhythmias may also lead to NIHF, with genetic etiologies including Costello, Barth, long QT, and Wolff‐Parkinson White syndromes . More rarely reported vascular disorders associated with NIHF include Klippel‐Trenaunay‐Weber syndrome, RASA1 ‐related disorders, and PIK3CA ‐associated segmental overgrowth syndromes .…”
Section: Genetic Causes Of Nihf By Organ Systemmentioning
confidence: 99%